Intentions of transport sector employees to leave the job: is workplace mobbing truly a catalyst? - Vveinhardt, Jolita; Domarkaitė, Simona; Deikus, Mykolas (Business: Theory and Practice, 2024)
Although previous studies have focused on workplace mobbing in transport companies, there is still a lack of research showing which variables have the greatest impact on employees’ intentions to leave their jobs. To address this gap, this paper aims to explore the workplace mobbing variables that strongly impact employees’ intentions to leave their workplaces in Lithuanian transport companies. Using the questionnaire “Mobbing and single cases of harassment in employees” relations – MSCH’, 440 employees of transport companies were surveyed. The performed analysis provided regression models aimed at reducing employees’ intentions to leave the workplace, eliminating regressors with the greatest negative influence, and at the same time, increasing the regressor with the most positive impact, i.e., prevention. The study revealed that abuse in assigning work tasks, poor self-feeling of employees, and experienced damage and prevention measures explained almost 45% of the dispersion in the intentions of transport sector employees to leave the job. In this context, the intervention measures used by the companies were not significant. The study shows that employees’ intentions to leave the job are most influenced by employees’ self-feeling, while prevention of workplace mobbing should be seen in a broader context, focusing on the ethics of managers’ relationships with employees. It also highlights the importance of creating a safe and trustworthy organisational environment and suggests that prevention strategies should address broader contexts, including abuse in task assignments, employees’ self-feeling, and the power dynamics of perpetrators.